From regional innovation systems to global innovation hubs: Evidence of a Quadruple Helix from an emerging economy - Malik, Ashish; Sharma, Piyush; Pereira, Vijay; Temouri, Yama (Elsevier, 2020)
Despite the growing importance of regional innovation systems as agglomerations of firms and actors that possess technical, leadership and managerial endowments for innovation and R&D activities, their impact on the evolution of global innovation hubs is still unclear. We address this gap by investigating the multiple influences of macro-, meso- and micro-level factors in the formation of global innovation hubs, using a comparative qualitative case study design with four MNEs operating in the Indian IT, pharma and healthcare sectors. We confirm the presence of ‘Communities of Practice’ as a fourth strand in our conceptualization of a Quadruple Helix in the emerging markets context. We also discover the critical role played by the interactions among communities of practice members and meso-level investments in organizational capabilities, learning and relationship quality. Finally, we highlight the importance of managing trust and power dynamics among members of communities of practice in a global innovation hub.